Red and golden tomato administration improves fat diet-induced hepatic steatosis in rats by modulating HNF4α, Lepr, and GK expression - Pipitone, Rosaria Maria; Zito, Rossella; Gambino, Giuditta; Di Maria, Gabriele; Javed, Ayesha; Lupo, Giulia; Giglia, Giuseppe; Sardo, Pierangelo; Ferraro, Giuseppe; Rappa, Francesca; Carlisi, Daniela; Di Majo, Danila; et al. (Frontiers in Nutrition, 2023)
Nonalcoholic fatty liver disease (NAFLD), characterized by the lipid accumulation within hepatocytes exceeding 5% of liver weight, whichstrictly related to metabolic disorders, obesity, and diabetes and represents a health emergency worldwide. .There is no standard therapy available for NAFLD, a key role is ascribed to lifestyle intervention including phytonutrient intake to prevent NAFLD development and progression. We have used a rat model of NAFLD to evaluate the effect of dietary supplementation with red tomato (RT) and golden tomato (GT), a patented mix of fruit with varying degrees of ripeness, particularly rich in naringenin and chlorogenic acid, after steatosis development. We have assessed the effects on body weight, metabolic profile, hepatic steatosis, a correlation between the amelioration of all the parameters and the liver gene expression was evidenced. Our results showed that, together with the reversion of steatosis, the consumption of RT and GT can cause a significant reduction in triglycerides, Low Density Lipoprotein-cholesterol, fasting glucose and homeostasis model assessment Index. In the meantime, the increase of Hight Density Lipoproteincholesterol was observed according to the general lipidic profile amelioration. In terms of hepatic gene expression, we found the up regulation of Gk and Hnf4a, involved in metabolic homeostasis, Lepr involved in adipokine signaling, and Il6 and Tnf involved in This is a provisional file, not the final typeset article inflammatory response. Taken together, our results suggest that dietary intake ofred and golden tomatoes, as a nutraceutical approach has potential in the prevention and therapeutics of NAFLD. .